Manifestações dermatológicas durante o tratamento da hepatite C crônica com interferon alfa peguilado e ribavirina - Leonardo Amedee Peret (2006)
Hepatitis C has become one of the most important diseases worldwide. Most of the patients infected by hepatitis C virus (HCV) develop chronic infection. Cirrhosis and hepatocellular carcinoma are the most important complications of the disease, but there are also extrahepatic manifestations. The cornerstone of the treatment is the use of a combination of interferon alfa and ribavirin. Although the recent introduction of a pegylated form of the interferon alfa (Peg-IFN alfa) has increased therapeutic response, the efficacy of the treatmentremains low. Side effects of these drugs are very common, and include flu-like syndrome, weight loss, depression, anemia and neutropenia. Dermatological manifestations associated with treatment in randomized trials have been described and the most common are alopecia,rash, pruritus and injection-site reactions. We sought to investigate the most common dermatological manifestations associated with the treatment of chronic hepatitis C with Peg- IFN alfa and ribavirin in a cohort of 46 patients. Patients were submitted to a complete dermatological evaluation prior to the treatment and for the first 24 weeks after the beginning of the drugs. The influence of other variables on the occurrence of dermatological manifestations was also evaluated, including age, sex, atopy, viral genotype, degree of hepatic fibrosis, previous exposition to the drugs and type of Peg-IFN prescribed (2a or 2b). The most common findings observed during the treatment were cutaneous xerosis (95,7%), xerostomia (79,1%), hair loss (65,9%), ichthyosis (50%) and pruritus (47,8%). Comparative analysis withpretreatment data showed statistically significant increase in the occurrence of these manifestations after the introduction of drug therapy. Photosensitivity (17,4%) and other cutaneous findings occurred in a small percentage of patients. Erythema and erythematousplaques were common in injection-sites of Peg-IFN alfa (76,1%). Older age was positively related to xerostomia and photosensitivity. Erythema and erythematous plaques at injectionsites were more related to Peg-IFN alfa 2b. Our results indicate an association between chronic hepatitis C treatment and the appearance of dermatological manifestations,particularly xerostomia, pruritus and hair loss. Cutaneous xerosis, ichthyosis and photosensitivity may also be related to treatment. Erythema and plaques at injection-sites are common and may be more frequent with Peg-IFN alfa 2b. Additional investigations are necessary to confirm these findings.